Harmonic Analysis of Large Grid-Connected PV Systems in Distribution Networks: A Saudi Case Study - Yahya M. Al-Sharif; Gamal M. Sowilam; Tamer A. Kawady (International Journal of Photoenergy)
The increasing penetration of grid-connected PV rooftops at the distribution level still entails significant technical challenges affecting seriously the power quality indices such as harmonics and voltage fluctuations. Owing to the intermittent nature of renewable resources, the changing incident energy from renewables can generate considerable amounts of harmonics. Moreover, power electronic devices and nonlinear loads that are used frequently in the industry may exaggerate the harmonic distortions as well. Accordingly, utilizing suitable filtration techniques for harmonic reduction is crucial. In order to evaluate the impacts of grid-connected PVs in modern grids, a case study on power quality and voltage profile is conducted with a large grid-connected PV microgrid of 9570 kW, feeding a large hospital project in Saudi Arabia as an initial phase of implementing this project in the future. For eliminating the possible increase in harmonic distortion, a single-tuned filter is used to cope with the permissible limits according to the known IEEE standards. This filtering technique is chosen due to its advantages including the simplicity, suitability for significant integer harmonic orders, and low cost. For evaluation tests, a detailed simulation is developed by the ETAP program for the overall selected project as well as the aimed PV subsystem. Several simulation tests are conducted to investigate the harmonic distortion problem. The results show a significant reduction in the individual harmonic distortion (IHD) and the total harmonic distortion (THD) below 8% according to considered IEEE standards for LV networks. Both 6 and 12 pule inverters are considered. This is considered an important step in the realization of such large PV projects in the field.